MENGINTIP KEBERADAAN ANAK DALAM AL-QUR’AN - ., Hasiah (Jurnal el-Qanuniy: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2020)
The child in the al-Qur’an contain two meanings, namely the child who are inter preted biologically and ideologically the child in the biologicall sense are position as the childcaused by birth, nasab or here ditary factors. The child in the ideologicall sense are position as the child caused by ties of value ties, such as whomanitarian valves, devotion, inner bonds and similarity of view